PENGARUH NET PROFIT MARGIN (NPM) DAN CAPITAL ADEQUANCY RATIO (CAR))TERHADAP HARGA SAHAM - Ahmad Darmawan; Ahmad Saeful Rahmatullah (Universitas La Tansa Mashiro, 2017)
This study aims to determine the effect of Net Profit Margin (NPM) and Capital Adequacy Ratio (CAR) on stock prices. This study uses banking samples from 2013-2016. Net Profit Margin (NPM), Capital Adequacy Rato (CAR) and stock prices are measured by looking at the financial statements of companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2016 period.The population in this study were 40 companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2016 period. After selection according to the purposive sampling method in the population, there are 10 banking companies that are used as samples. This study used a quantitative method with a descriptive approach to determine the effect between Net profit margin (NPM) and Capital Adequacy Ratio (CAR) on stock prices, using secondary data and data analysis techniques using multiple regression analysis.Based on the results of the study, Net Profit Margin (NPM) has a positive and significant effect on stock prices in banking companies listed on the Indonesia stock exchange (BEI) in 2013-2016, with a positive regression coefficient and t-value of 2.338 significant 0.023 and Capital Adequacy Ratio (CAR) has a positive and significant effect on stock prices in banking companies listed on the Indonesian stock exchange (BEI) in 2013-2016 with a positive regression coefficient and a t-value of 0.325 significant 0.012.